Animation Movies: Are They Entertaining or Threatening For Children? - Hasanah, Nur; Octaviana, Eva (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Western animation movies emerge tremendously as an entertainment that can be one of the alternative way for parents to spend their leisure time with their children. The movies are interesting because of their features which has been created with cheerful and colorful nuance, uncanny animation and interesting story. In Indonesia, Western animation movies commonly are rated as all age although some of them should make any parents worried as their contents often consist of violent and sexual packing.  This article tries to uncover the phenomenon of these movies and how they can negatively affect children. It uses literature review as a technique to dig in the problem. The negative effects of animation movies have become a threat for children for some prominent reasons. Western animation movies should be considered as one of entertainment media with its consequences and it is better to observe thoroughly before letting the children watch.